Production and sequence validation of a complete full length ORF collection for the pathogenic bacterium Vibrio cholerae - Rolfs, Andreas (National Academy of Sciences, 2008)
Cholera, an infectious disease with global impact, is caused by pathogenic strains of the bacterium Vibrio cholerae. High-throughput functional proteomics technologies now offer the opportunity to investigate all aspects of the proteome, which has led to an increased demand for comprehensive protein expression clone resources. Genome-scale reagents for cholera would encourage comprehensive analyses of immune responses and systems-wide functional studies that could lead to improved vaccine and therapeutic strategies. Here, we report the production of the FLEXGene clone set for V. cholerae O1 biovar eltor str. N16961: a complete-genome collection of ORF clones. This collection includes 3,761 sequence-verified clones from 3,887 targeted ORFs (97%). The ORFs were captured in a recombinational cloning vector to facilitate high-throughput transfer of ORF inserts into suitable expression vectors. To demonstrate its application, ≈15% of the collection was transferred into the relevant expression vector and used to produce a protein microarray by transcribing, translating, and capturing the proteins in situ on the array surface with 92% success. In a second application, a method to screen for protein triggers of Toll-like receptors (TLRs) was developed. We tested in vitro-synthesized proteins for their ability to stimulate TLR5 in A549 cells. This approach appropriately identified FlaC, and previously uncharacterized TLR5 agonist activities. These data suggest that the genome-scale, fully sequenced ORF collection reported here will be useful for high-throughput functional proteomic assays, immune response studies, structure biology, and other applications.